2014
DOI: 10.14719/pst.2014.1.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential therapeutic targets of a natural product Jujuboside B for insomnia through network pharmacology

Abstract: Knowledge of the interactome improves the understanding of disease metabolism. Biological information about interactions among genes and their protein products, computationally extracted in the context of SysBiomics, can hint at molecular causes of diseases, be essential for understanding biological systems, and provide clues for new therapeutic approaches. Quick and efficient access to this data have become critical issues for biologists. We have implemented a computational platform that integrates pathway, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Spinosin has also been reported to potentiate pentobarbital-induced sleep via a serotonergic mechanism while 6 ‴ -feruloylspinosin has been proven to induce the prolongation of hexobarbital sleeping time in mice [ 9 , 10 ]. JuA and JuB are the major saponins, and both exhibit the hypnotic effect by adjusting the mRNA expression of GABA receptor subunit and partially regulating the amino-acid metabolism pathway [ [11] , [12] , [13] ]. Recent studies indicate that magnoflorine has sedative and anxiolytic effects, and coclaurine causes sedative bioactivity by interacting with melatonin receptors [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spinosin has also been reported to potentiate pentobarbital-induced sleep via a serotonergic mechanism while 6 ‴ -feruloylspinosin has been proven to induce the prolongation of hexobarbital sleeping time in mice [ 9 , 10 ]. JuA and JuB are the major saponins, and both exhibit the hypnotic effect by adjusting the mRNA expression of GABA receptor subunit and partially regulating the amino-acid metabolism pathway [ [11] , [12] , [13] ]. Recent studies indicate that magnoflorine has sedative and anxiolytic effects, and coclaurine causes sedative bioactivity by interacting with melatonin receptors [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 It can monitor and quantify the changes in small molecule metabolites, such as fatty acids, amino acids, peptides, nucleic acids, organic acids, vitamins, and carbohydrates, in an organism or a biological sample during the ultimate response to the endogenous and exogenous factors. 13 Metabolomics can systematically and holistically probe the metabolome and metabolic pathway variations to explore the efficacy of a therapy, particularly that of TCM, which is difficult to study using conventional pharmacological methods due to its multi-component and multi-target peculiarity. 14 Currently, metabolomics has been successfully applied to detect metabolic changes in sepsis and characterize biochemical pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the control group, PE(20:4 (8Z,11Z,14Z,17Z)/15:0) was lower and PE(14:1(9Z)/24:1(15Z)) was increased in the model group, indicating that abnormal material identication and transport occurred in the cell, which has been shown to cause metabolic disorders. 23 Some studies have shown that for cholesterol to function properly in the body and to show proper metabolism, it must be combined with linoleic acid. Body lipid metabolism disorders caused by insufficient amounts of linoleic acid have been shown to result in reduced immunity, forgetfulness, fatigue, vision loss and other symptoms.…”
Section: Discussionmentioning
confidence: 99%